Analysis of the Effect of Musyarakah Financing on Net Profit and Profit-Sharing: A Study on Bank Syariah Indonesia - Sasmita, Lintang Auliya; Setiawan, Nanang (Institut Agama Islam Al-Fatimah Bojonegoro, 2025)
This study aims to analyze the effect of musyarakah financing on net profit and profit-sharing at Bank Syariah Indonesia. The research employs a descriptive quantitative method with regression analysis, utilizing secondary data obtained from the financial reports of Bank Syariah Indonesia for the 2020 to 2023 period. The findings reveal that musyarakah financing has a significant positive effect on net profit. An increase in musyarakah financing has been proven to drive net profit growth, which subsequently contributes to the enhancement of profit-sharing distribution to shareholders and customers. These findings emphasize that musyarakah financing not only aligns with Sharia principles but also serves as an effective strategy to improve the financial performance of Islamic banks. Thus, musyarakah financing can be a viable solution within the Islamic banking system, particularly in supporting profitability and business sustainability. This study recommends that Bank Syariah Indonesia further optimize musyarakah financing as one of the main instruments in Sharia financial management, focusing on increasing net profit and profit-sharing